Upwelling Amplifies Ocean Acidification on the East Australian Shelf: Implications for Marine Ecosystems - Schulz, Kai G.; Hartley, Simon; Eyre, Bradley (Frontiers in Marine Science, 2019)
Frequent upwelling of cold deep water rich in dissolved inorganic nutrients but low in oxygen concentrations and pH is well documented in so-called Eastern-boundary systems. As a consequence vast areas of the continental shelf can turn corrosive to the mineral aragonite, vital to a number of marine organisms. This phenomenon is projected to become more severe with ongoing ocean acidification. Although upwelling is also known to occur in Western-boundary systems, the impact on present day aragonite saturation state (Ω arag ) is virtually unknown, let alone for the decades to come. Here we identified 37 events during 18 weeks of continuous measurements in Cape Byron Marine Park, Australia, by prolonged drops in ocean temperature of up to 5 ◦ C, oxygen concentrations by 34%, pH by 0.12 and Ω_arag by 0.9 units in a matter of hours. Extrapolating present day upwelling to a Pre-Industrial setting shows that ongoing ocean acidification has already lead to the crossing of a number of biological and geochemcial Ω_arag thresholds. If representative for the East Australian shelf, modelling further suggests that coral reefs with low coral cover could become net dissolving within the next 30 years. With the Great Barrier Reef estimated to currently contribute more than A$6 billion annually to the Australian economy, this would come at a considerable financial cost.